Acoustic Features Influence Musical Choices Across Multiple Genres - Barone, Michael D.; Bansal, Jotthi; Woolhouse, Matthew H. (Frontiers in Psychology, 2017)
Based on a large behavioral dataset of music downloads, two analyses investigate whether the acoustic features of listeners’ preferred musical genres influence their choice of tracks within non-preferred, secondary musical styles. Analysis 1 identifies feature distributions for pairs of genre-defined subgroups that are distinct. Using correlation analysis, these distributions are used to test the degree of similarity between subgroups’ main genres and the other music within their download collections. Analysis 2 explores the issue of main-to-secondary genre influence through the production of ten feature-influence matrices, one per acoustic feature, in which cell values indicate the percentage change in features for genres and subgroups compared to overall population averages. In total, ten acoustic features and ten genre-defined subgroups are explored within the two analyses. Results strongly indicate that the acoustic features of people’s main musical genres influence the other styles they download. The nature of this influence and its possible actuating mechanisms are discussed with respect to research on personality, mood, musical preference, and statistical learning.